2023
DOI: 10.3390/ijms241512531
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of L1CAM with LC3 Is Required for L1-Dependent Neurite Outgrowth and Neuronal Survival

Abstract: The neural cell adhesion molecule L1 (also called L1CAM or CD171) functions not only in cell migration, but also in cell survival, differentiation, myelination, neurite outgrowth, and signaling during nervous system development and in adults. The proteolytic cleavage of L1 in its extracellular domain generates soluble fragments which are shed into the extracellular space and transmembrane fragments that are internalized into the cell and transported to various organelles to regulate cellular functions. To iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Since interactions of L1 with methyl CpG binding protein 2, estrogen receptor and retinoid X receptor were similar in wild-type and L1/687 neurons [27,33], we can assume that certain heterophilic interaction partners can interact with full-length L1 carrying the R/A687 mutation or with L1 fragments generated in L1/687 mice. In contrast, other heterophilic interactions depend on L1-70, like the interaction of L1 with microtubule-associated protein 1A/1B-light chain 3, and these are disturbed in L1/687 mice [55] and can contribute to the mutant phenotype. Our findings help to explain how mutations in L1 differently alter brain development and functioning, leading to moderate to severe L1 syndrome phenotypes, suggesting that enhancing mitochondrial and neuronal functions in L1 syndrome patients could help to ameliorate L1 syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since interactions of L1 with methyl CpG binding protein 2, estrogen receptor and retinoid X receptor were similar in wild-type and L1/687 neurons [27,33], we can assume that certain heterophilic interaction partners can interact with full-length L1 carrying the R/A687 mutation or with L1 fragments generated in L1/687 mice. In contrast, other heterophilic interactions depend on L1-70, like the interaction of L1 with microtubule-associated protein 1A/1B-light chain 3, and these are disturbed in L1/687 mice [55] and can contribute to the mutant phenotype. Our findings help to explain how mutations in L1 differently alter brain development and functioning, leading to moderate to severe L1 syndrome phenotypes, suggesting that enhancing mitochondrial and neuronal functions in L1 syndrome patients could help to ameliorate L1 syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we showed that L1-70 interacts with microtubuleassociated protein 1A/1B-light chain 3, topoisomerase I, peroxisome proliferator-activated receptor γ and β-nicotinamide adenine dinucleotide hydrate dehydrogenase (ubiquinone) flavoprotein 2, and, in L1/687 cells, these interactions did not take place. In contrast, the retinoid X receptor, estrogen receptor α, splicing factor proline/glutamine-rich, non-POU domain-containing octamer-binding protein and paraspeckle component 1 interacted with L1 with R687V mutation and did not bind to L1-70 [27,55]. We analyzed in vivo the influence of the R to A substitution at position 687 of L1 on brain development and nervous system functions in adult mice.…”
Section: Introductionmentioning
confidence: 99%
“…L1-CAM is expressed in the central nervous system by subpopulations of neurons and on glial cells in the peripheral nervous system ( Rathjen and Schachner, 1984 ; Seilheimer and Schachner, 1987 ). L1-CAM is involved in adhesion between neurons, the formation of neural fiber bundles, and the growth of nerve processes ( Moos et al, 1988 ; Wang et al, 2012 ; Congiu et al, 2022 ; Loers et al, 2023 ). It mediates homophilic and heterophilic interactions between neurons ( Kadmon et al, 1990a ; Sytnyk et al, 2017 ; Stoyanova and Lutz, 2022 ) and cooperates with NCAM through a mechanism termed assisted homophilic adhesion ( Kadmon et al, 1990b ).…”
Section: Associations Between Synaptic Adhesion Molecules and Fxsmentioning
confidence: 99%
“…According to the findings of Loers et al (2023) , L1 siRNA has an inhibitory effect on the expression of long-chain autism genes neurexin 1 ( NRXN1 ) and neuroligin 1 ( NLGN1 ) and mitochondrial-encoding genes such as NADH ubiquinone oxidoreductase core subunit 2 ( ND2 ). Additionally, Lai et al (2016) found that FMRP binds to NLGN1 and NLGN3 mRNA, whereas Dahlhaus and El-Husseini (2010) revealed an association between the core symptoms of FXS and the neurexin-neuroligin network.…”
Section: Associations Between Synaptic Adhesion Molecules and Fxsmentioning
confidence: 99%